GROWTH PATTERNS AND GONAD MATURITY LEVELS OF (Barbonymus schwanefeldii) FISH IN THE BATANG ASAI SAROLANGUN RIVER - Yoppie Wulanda; Rizky Janatul Magwa; Ester Restiana Endang Gelis; Septy Heltria; Lauura Hermala Yunita; Farhan Ramdhani; Febrina Rolin; Yusyam Leni; Muhammad Hafidz Ibnu Khaldun; Ainun Rohmawati Bareta (Asian Journal of Aquatic Sciences, 2025)
The condition of the Batang Asai River in Sarolangun Regency, Jambi, has experienced a decline in water quality due to anthropogenic activities such as land clearing, settlement, and mining. This condition threatens the sustainability of fish populations, especially those from the Cyprinidae family, which are an important and environmentally sensitive group of fish for consumption, one of which is the lampam (Barbonymus schwanefeldii). However, scientific information on the bioecology of lampam in this region is very limited. Therefore, this research is needed to provide basic data to support adaptive conservation and fisheries management strategies. This study aims to analyze the growth patterns and gonadal maturity levels of lampam in the Batang Asai River, Sarolangun Regency, as a basis for inland fisheries management. A total of 113 fish, consisting of 64 males and 49 females, were observed. Male fish had a positive allometric growth pattern, while female fish had an isometric growth pattern. Analysis of Gonad Maturity Level (GML) found fish with GML I to GML IV, but immature gonads dominated the condition of the fish. In general, the water quality of the Batang Asai River still supports fish life, as can be seen from the growth patterns of the fish, but most of the fish found during the study were still immature despite the presence of fish with GML I to GML IV.